2015
DOI: 10.1038/ncomms9758
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the mycotoxin tenuazonic acid by a fungal NRPS–PKS hybrid enzyme

Abstract: Tenuazonic acid (TeA) is a well-known mycotoxin produced by various plant pathogenic fungi. However, its biosynthetic gene has been unknown to date. Here we identify the TeA biosynthetic gene from Magnaporthe oryzae by finding two TeA-inducing conditions of a low-producing strain. We demonstrate that TeA is synthesized from isoleucine and acetoacetyl-coenzyme A by TeA synthetase 1 (TAS1). TAS1 is a unique non-ribosomal peptide synthetase and polyketide synthase (NRPS–PKS) hybrid enzyme that begins with an NRPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 64 publications
3
124
1
1
Order By: Relevance
“…1). Further secondary metabolites previously described to be produced by the rice blast fungus, for example, pyrichalasin H [31], pyriculol [32] or tenuazonic acid [12][13][14], were not found in this study. Based on considerations concerning the chemical structure of pyriculol, we searched for PKS-encoding genes in the genome of M. oryzae.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…1). Further secondary metabolites previously described to be produced by the rice blast fungus, for example, pyrichalasin H [31], pyriculol [32] or tenuazonic acid [12][13][14], were not found in this study. Based on considerations concerning the chemical structure of pyriculol, we searched for PKS-encoding genes in the genome of M. oryzae.…”
Section: Discussioncontrasting
confidence: 73%
“…Additional studies have identified other metabolites produced by Magnaporthe strains, i.e. tenuazonic acid and Magtoxin [10,[12][13][14]. Tenuazonic acid is a mycotoxin synthesized by various plant pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanin, a polyketide compound, is biosynthesized by the PKS ALB1/MGG_07219 and modifying enzymes . Tenuazonic acid is biosynthesized by a unique NRPS–PKS enzyme: TAS1/MGG_07803 . Pyriculols are polyketide compounds, and the identification of the pyriculol biosynthetic gene cluster containing the PKS gene MoPKS19 / MGG_10912 was reported recently .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that knockout of the HOG MAP kinase gene OSM1 , which works downstream of the TCS, can activate the production of tenuazonic acid in P. oryzae . Herein, we show that the production of other secondary metabolites can be activated by double gene knockout of OSM1 and PoYPD1 ( MoYPD1 ), which encodes an HPt.…”
Section: Introductionmentioning
confidence: 99%